2015
DOI: 10.1039/c5cp02525g
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric and fluorimetric response of Schiff base molecules towards fluoride anion, solution test kit fabrication, logical interpretations and DFT-D3 study

Abstract: Two newly synthesized Schiff base molecules are herein reported as anion sensors. -NO2 substituted receptor (P1) is comparatively more acidic and can sense F(-), OAc(-) and H2PO4(-), whereas -CN substituted receptor (P2) is less acidic and is selective for F(-) only. Reversible UV-Vis response for both receptors with F(-) can mimic multiple logic gate functions, and several complex electronic circuits based on XNOR, XOR, OR, AND, NOT and NOR logic operations with 'Write-Read-Erase-Read' options have been execu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…The enhancement of the ICT transition could be ascribed to a push–pull nature between the electron withdrawing –CN substituent and the conjugated system [39]. The appearance of a clear isosbestic point at 443 nm indicates the existence of a host–guest complex in the system.…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement of the ICT transition could be ascribed to a push–pull nature between the electron withdrawing –CN substituent and the conjugated system [39]. The appearance of a clear isosbestic point at 443 nm indicates the existence of a host–guest complex in the system.…”
Section: Resultsmentioning
confidence: 99%
“…Receptor 1 studied here upon complexation Cu 2+ showed selective fluorescence quenching when compared with other tested metal ions. Compared with receptors based on imidazole, amide, urea and thiourea possessing multiple –NH groups preferred mainly to detect anions . The use of Schiff bases is advantageous due to their easy one‐step synthesis; the presence of conjugated bonds gave excellent optical properties that could be tuned to develop chemosensors for different metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the downside of this type of chemosensor is that other anions, such as AcO – and H 2 PO 4 – may cause significant interference . It is reported that the selectivity if an anion chemosensor in related to the structure of the hydrogen bond complex and the basicity of the anions . Therefore, the higher basicity of F – compared to other anions is commonly exploited as the basis for the construction of F – ‐specific chemosensors …”
Section: Introductionmentioning
confidence: 99%